Gas barrier film and barrier laminate

By using polypropylene or polyethylene in the base layer and heat sealing layer of the gas barrier film, and adjusting the polar component value of the surface free energy during the peeling test, the adhesion of the gas barrier layer in the gas barrier film was solved. The problem of insufficient achieves more efficient adhesion evaluation and single materialization.

CN119451821APending Publication Date: 2025-02-14TOPPAN HOLDINGS INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380050930.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-07-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When using a gas barrier film as the intermediate layer of a multi-layer laminated film, the surface adhesion of the gas barrier layer without forming is insufficient, resulting in chain breakage in the peeling test, and it is difficult to accurately evaluate the adhesion.

Method used

A base material layer with polypropylene or polyethylene as the main component is used to form a gas barrier layer on the first side of the surface, and a heat seal layer is formed on the second side of the opposite side to ensure separation between the base material layer and the heat seal layer. The intensity is within a specified range, and the polar component value of the surface free energy of the second surface is adjusted to improve adhesion.

Benefits of technology

The adhesion of the surface where the gas barrier layer is not formed is achieved is good, the chain breakage phenomenon in the peeling test is reduced, and the adhesion of the multi-layer laminated film can be more accurately evaluated, and the single materialization can be promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451821A_ABST
    Figure CN119451821A_ABST
Patent Text Reader

Abstract

This gas barrier film is provided with: a base material layer having polypropylene or polyethylene as the main component; a gas barrier layer formed on a first surface side of the substrate layer; and a heat sealing layer which is formed on a second surface opposite to the first surface and has polypropylene or polyethylene as a main component. The peel strength between the base material layer and the heat sealing layer is 1.0 N / 15 mm or more and 7.0 N / 15 mm or less in 180 DEG peeling in accordance with JIS K 6854-2, and 1.0 N / 15 mm or more and 4.0 mm / 15 mm or less in T-shaped peeling in accordance with JIS K 6854-3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a gas barrier film using a resin substrate and also to a barrier laminate using the gas barrier film.

[0002] This application claims priority from Tokugan Application No. 2022-111829 filed in Japan on July 12, 2022, and Tokugan Application No. 2022-111830 filed in Japan on July 12, 2022, and the contents of which are incorporated herein by reference. Background Art

[0003] Gas barrier films are films that do not allow oxygen and water vapor to pass through (gas barrier properties). From the perspective of suppressing the deterioration of the contents and maintaining their functions and properties, they are widely used in various fields that require isolation from various gases, such as packaging of precision electronic components, electronic components, food, and pharmaceuticals.

[0004] In recent years, as environmental awareness has been growing due to issues such as marine plastic waste, there has been a demand for more efficient recycling and separation of plastic materials. Gas barrier films, which have previously achieved high performance by combining various materials, are no exception, and there is now a demand for single-material films.

[0005] In order to achieve a single material, it is necessary to increase the ratio of the resin used most in the gas barrier film. As an example of such a structure, Patent Document 1 discloses a barrier film using polyethylene as a substrate and having an aluminum oxide vapor-deposited film formed thereon.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2019 / 087960 Summary of the invention

[0009] Problems to be solved by the invention

[0010] When the gas barrier film is used as an intermediate layer of a multilayer laminate film, the surface of the multilayer laminate film where the gas barrier layer is not formed requires adhesion with an adhesive or ink layer. In Patent Document 1, although attention is paid to the adhesion between the substrate and the alumina vapor-deposited film, no attention is paid to the surface where the vapor-deposited film is not formed.

[0011] In addition, as a method for evaluating the adhesion of a multilayer laminated film, a peel test according to JIS K 6854-2 and JIS K6854-3 is widely used. In this peel test, a phenomenon called "zipping" sometimes occurs: peeling cannot be performed smoothly, and the peeling is repeated and stopped alternately. When zipping occurs in a peel test (also called a peel test), the adhesion of the multilayer laminated film may not be accurately evaluated. As a result, it is difficult to determine whether the manufactured film meets the required characteristics.

[0012] In view of the above circumstances, an object of the present invention is to provide a gas barrier film and a barrier laminate having good adhesion on the surface where a gas barrier layer is not formed and which can be easily made into a single material.

[0013] Means for solving problems

[0014] The present invention has the following aspects.

[0015] [1] A gas barrier film comprising: a substrate layer mainly composed of polypropylene or polyethylene; a gas barrier layer formed on a first surface side of the substrate layer; and a heat seal layer mainly composed of polypropylene or polyethylene formed on a second surface opposite to the first surface, wherein the peel strength between the substrate layer and the heat seal layer is 1.0 N / 15 mm to 7.0 N / 15 mm in 180° peeling according to JIS K 6854-2, and is 1.0 N / 15 mm to 4.0 mm / 15 mm in T-peeling according to JIS K 6854-3.

[0016] [2] The gas barrier film according to [1], wherein the polar component value of the surface free energy of the second surface opposite to the first surface is 0.1 mJ / m 2 above.

[0017] [3] The gas barrier film according to [1], wherein the second surface opposite to the first surface is composed of a copolymer and the polar component value of the surface free energy is 0.1 mJ / m 2 above.

[0018] [4] The gas barrier film according to any one of [1] to [3], wherein the polar component value of the surface free energy of the second surface is less than 1.3 mJ / m 2 .

[0019] [5] The gas barrier film according to any one of [1] to [4], wherein the gas barrier layer contains at least one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide.

[0020] [6] The gas barrier film according to any one of [1] to [5], wherein the first surface is made of any one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, a composite of polypropylene, polyethylene and α-olefin, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer.

[0021] [7] The gas barrier film according to any one of items [1] to [6], further comprising a coating layer formed on the gas barrier layer, the coating layer containing any one of a metal alkoxide, a hydrolyzate of a metal alkoxide, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, and a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e., a polyvalent metal salt of a carboxylic acid.

[0022] [8] The gas barrier film according to any one of [1] to [7], further comprising a primer layer provided between the first surface and the gas barrier layer, the primer layer comprising at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet curable resin, and an electron beam curable resin.

[0023] [9] The gas barrier film according to [1] or [2], wherein the peel strength between the substrate layer and the heat seal layer is 2.0 N / 15 mm or more and 7.0 N / 15 mm or less in 180° peeling according to JIS K 6854-2.

[0024]

[10] The gas barrier film according to [3], wherein the difference between the maximum value and the minimum value of the peel strength in the 180° peeling is less than 0.3 N / 15 mm.

[0025]

[11] A barrier laminate comprising: the gas barrier film according to any one of [1] to

[10] ; and a heat seal layer having the same main component as the substrate layer and bonded to the gas barrier film.

[0026]

[12] The barrier laminate according to

[11] , further comprising a surface layer having the same main component as that of the substrate layer and bonded to the gas barrier film.

[0027]

[13] The barrier laminate according to

[12] , wherein at least one of the heat seal layer and the surface layer is bonded to the gas barrier film via an adhesive.

[0028]

[14] The barrier laminate according to

[12] or

[13] , wherein the surface layer has a printed layer on at least one surface.

[0029] In one aspect, the present invention has the following aspects.

[0030] [A1] A gas barrier film comprising: a base layer mainly composed of polypropylene or polyethylene; and a gas barrier layer formed on a first surface side of the base layer.

[0031] In the gas barrier film, the polar component value of the surface free energy of the second surface opposite to the first surface is less than 0.1 mJ / m 2 .

[0032] [A2] The gas barrier film according to [A1], wherein the polar component value of the surface free energy of the second surface is less than 1.3 mJ / m 2 .

[0033] [A3] The gas barrier film according to [A1] or [A2], wherein the gas barrier layer contains at least one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide.

[0034] [A4] The gas barrier film according to any one of [A1] to [A3], wherein the first surface is composed of any one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, a composite of polypropylene, polyethylene and α-olefin, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer.

[0035] [A5] The gas barrier film according to any one of items [A1] to [A4] further comprises a coating layer formed on the gas barrier layer, wherein the coating layer contains any one of a metal alkoxide, a hydrolysis product of a metal alkoxide, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, and a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e. a polyvalent metal salt of a carboxylic acid.

[0036] [A6] The gas barrier film according to any one of [A1] to [A5], further comprising a primer layer arranged between the first surface and the gas barrier layer, the primer layer comprising at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet curable resin, and an electron beam curable resin.

[0037] [A7] A barrier laminate comprising: the gas barrier film according to any one of [A1] to [A6]; and a heat seal layer having the same main component as the substrate layer and bonded to the gas barrier film.

[0038] [A8] The barrier laminate according to [A7], further comprising a surface layer having the same main component as that of the substrate layer and bonded to the gas barrier film.

[0039] [A9] The barrier laminate according to [A8], wherein at least one of the heat seal layer and the surface layer is bonded to the gas barrier film via an adhesive.

[0040] [A10] The barrier laminate according to [A8] or [A9], wherein the surface layer has a printed layer on at least one surface.

[0041] As still another aspect, the present invention has the following aspects.

[0042] [B1] A gas barrier film comprising: a base layer containing polypropylene or polyethylene as a main component; and a gas barrier layer formed on a first surface side of the base layer.

[0043] In the gas barrier film, the second surface opposite to the first surface is composed of a copolymer, and the polar component value of the surface free energy is less than 0.1 mJ / m 2 .

[0044] [B2] The gas barrier film according to [B1], wherein the polar component value of the surface free energy of the second surface is less than 1.3 mJ / m 2 .

[0045] [B3] The gas barrier film according to [B1] or [B2], wherein the gas barrier layer contains at least one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide.

[0046] [B4] The gas barrier film according to any one of [B1] to [B3], wherein the first surface is composed of any one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, a composite of polypropylene, polyethylene and α-olefin, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer.

[0047] [B5] The gas barrier film according to any one of items [B1] to [B4] further comprises a coating layer formed on the gas barrier layer, wherein the coating layer contains any one of a metal alkoxide, a hydrolysis product of a metal alkoxide, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, and a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e., a polyvalent metal salt of a carboxylic acid.

[0048] [B6] The gas barrier film according to any one of [B1] to [B5], further comprising a primer layer arranged between the first surface and the gas barrier layer, the primer layer comprising at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet curable resin, and an electron beam curable resin.

[0049] [B7] A barrier laminate comprising: the gas barrier film according to any one of [B1] to [B6]; and a heat seal layer having the same main component as the substrate layer and bonded to the gas barrier film.

[0050] [B8] The barrier laminate according to [B7], further comprising a surface layer having the same main component as that of the substrate layer and bonded to the gas barrier film.

[0051] [B9] The barrier laminate according to [B8], wherein at least one of the heat seal layer and the surface layer is bonded to the gas barrier film via an adhesive.

[0052] [B10] The barrier laminate according to [B8] or [B9], wherein the surface layer has a printed layer on at least one surface.

[0053] Effects of the Invention

[0054] According to the present invention, it is possible to provide a gas barrier film and a barrier laminate having good adhesion on the surface where the gas barrier layer is not formed and which can be easily made into a single material. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] [ Figure 1 ] is a schematic cross-sectional view of a gas barrier film according to one embodiment of the present invention.

[0056] [ Figure 2 ] is a schematic cross-sectional view showing an example of a barrier laminate using the gas barrier film.

[0057] [ Figure 3 ] is a schematic cross-sectional view showing another example of a barrier laminate using the gas barrier film.

[0058] [ Figure 4 ] is a graph showing the peel test results of the comparative example. DETAILED DESCRIPTION

[0059] <First Embodiment>

[0060] Below, refer to Figure 1 A first embodiment of the present invention will be described.

[0061] Figure 1 Schematic cross-sectional view of the gas barrier film 1 according to the present embodiment. The gas barrier film 1 includes a base layer 10 , a gas barrier layer 20 formed on a first surface 10 a of the base layer 10 , and a covering layer 30 covering the gas barrier layer 20 .

[0062] The substrate layer 10 is a resin film with polypropylene or polyethylene as the main component. The substrate layer 10 can be any of an unstretched film and a stretched film. In the case of using a stretched film, there is no particular restriction on the stretch ratio. In addition, there is no particular restriction on the thickness of the substrate layer 10. Considering the use of the packaging material, the substrate layer 10 can be a single-layer film or a multilayer film formed by laminating films of different properties. Considering the processability when forming the gas barrier layer 20 and the coating layer 30, the thickness of the substrate layer 10 is preferably in the range of 3 to 200 μm in practical use, and particularly preferably 6 to 50 μm. In addition, the substrate layer 10 can be in the form of a long strip material or a sheet cut into a specified size, but a long strip substrate can be preferably used. There is no particular restriction on the longitudinal length of the long strip substrate layer 10, for example, it is preferred to use a long strip film of more than 10 m. It should be noted that since there is no upper limit on the length, it can be, for example, about 10 km. In this case, by rolling it into a roll, it can be efficiently transported and stored.

[0063] The "main component" of the base layer 10 refers to the substance with the largest mass among the substances constituting the base layer 10. In addition, in the present embodiment, the "main component" of each component refers to the substance with the largest mass among the substances constituting each component.

[0064] When the main component of the base material layer 10 is set to polypropylene, the main component of the base material layer 10 is not limited to the resin obtained by polymerizing only propylene, and a resin containing substances other than propylene can be used. For example, a copolymer obtained by copolymerizing polyethylene such as HDPE (high-density polyethylene), MDPE (medium-density polyethylene), LDPE (low-density polyethylene), and LLDPE (linear low-density polyethylene) with propylene at a ratio of 0.1 to several tens of percent; a multimer obtained by copolymerizing α-olefin resins such as 1-butene or / and rubber components such as elastomers with propylene or ethylene at a ratio of 0.1 to several tens of percent, etc. In addition, a layer in which multiple resins are mixed and dispersed instead of copolymerized can also be used.

[0065] When the main component of the base material layer 10 is polyethylene, the polyethylene resin may be selected from any one or more of HDPE, LDPE, MDPE, and LLDPE. In addition, a copolymer or multimer obtained by copolymerizing ethylene with an α-olefin resin such as 1-butene or / and a rubber component such as an elastomer at a ratio of 0.1 to several tens of percent may also be used.

[0066] The substrate layer 10 may be a multilayer film obtained by laminating films of different properties. In this case, in the substrate layer 10, a layer composed of any one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, a composite of polypropylene, polyethylene and α-olefin, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer may be provided on the surface serving as the first surface 10a.

[0067] When the substrate layer 10 is formed into multiple layers, the substrate layer 10 may include a layer having polypropylene or polyethylene as a main component and a layer not containing the main component. For example, when the layer constituting the first surface 10a is a layer consisting only of PVA (polyvinyl alcohol) or EVOH (ethylene-vinyl alcohol copolymer), the barrier properties of the gas barrier film 1 can be improved.

[0068] The substrate layer 10 having a plurality of layers (also referred to as a multilayer substrate) can be formed by pasting a plurality of films using an adhesive, or by coextrusion using a plurality of screws, etc. For a multilayer substrate formed by coextrusion, the boundaries of the layers cannot be clearly confirmed even by observation using an optical microscope, but the boundaries of the layers can be confirmed by observing the cross section using a transmission electron microscope (TEM) after appropriate staining.

[0069] The substrate layer 10 may contain additives that are not resin components. As additives, they can be appropriately selected from various well-known additives. Examples of additives include: anti-blocking agents (AB agents), heat stabilizers, weather stabilizers, ultraviolet absorbers, lubricants, slip agents, nucleating agents, antistatic agents, antifogging agents, pigments, and dyes. AB agents can be organic or inorganic. Any one of these additives can be used alone, or two or more can be used in combination. From the viewpoint of processing adaptability, lubricants and slip agents among the above can be listed as preferred additives. The content of the additives in the substrate layer 10 can be appropriately adjusted within a range that does not hinder the effect of the gas barrier film of this embodiment.

[0070] The gas barrier layer 20 is a layer of a single substance or a mixture having any one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide as a main component, and has a barrier property against a predetermined gas such as oxygen and water vapor. A plurality of main components having the largest mass may also exist in the gas barrier layer 20. The gas barrier layer 20 may be transparent or opaque.

[0071] The thickness of the gas barrier layer 20 varies depending on the type / composition / film forming method of the components used, and can generally be appropriately set within the range of 3 to 300 nm. When the thickness of the gas barrier layer 20 is less than 3 nm, a uniform film may not be obtained or the film thickness is insufficient, and the function as a gas barrier layer may not be fully exerted. When the thickness of the gas barrier layer 20 exceeds 300 nm, after film formation, cracks may occur in the gas barrier layer 20 due to external factors such as bending and stretching, and the barrier properties may be lost. The thickness of the gas barrier layer 20 is more preferably within the range of 6 to 150 nm.

[0072] There is no limitation on the method for forming the gas barrier layer 20, and for example, vacuum evaporation, plasma activated evaporation, ion beam evaporation, ion plating, sputtering, and plasma vapor deposition (CVD) can be used. When a plasma-assisted method or an ion beam-assisted method is used in combination, the gas barrier layer 20 can be densely formed to improve the barrier property and adhesion.

[0073] The covering layer 30 covers and protects the gas barrier layer 20, and further improves the barrier properties of the gas barrier film 1. The covering layer 30 is an arbitrary structure, and may be omitted.

[0074] The coating layer 30 can be made of a coating of a thermoplastic resin, a thermosetting resin, an ultraviolet curing resin, a metal alkoxide or its hydrolyzate, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e., a polyvalent metal salt of a carboxylic acid. A coating containing a metal alkoxide and a water-soluble polymer having excellent oxygen barrier properties is particularly preferred. The coating is formed using a coating agent having as a main agent an aqueous solution or a water / alcohol mixed solution containing a water-soluble polymer and one or more metal alkoxides or their hydrolyzates. For example, a coating agent is prepared by directly mixing a metal alkoxide with a solution obtained by dissolving a water-soluble polymer in an aqueous (water or water / alcohol mixed) solvent, or by mixing a substance obtained by pre-hydrolyzing the metal alkoxide. The coating agent is applied to the gas barrier layer 20 and then dried, thereby forming the coating layer 30.

[0075] The components contained in the coating agent for forming the coating layer 30 are described in more detail. As water-soluble polymers used in the coating agent, PVA, polyvinyl pyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, and sodium alginate can be exemplified. In particular, when PVA is used, excellent gas barrier properties can be obtained, so it is preferred. PVA is generally obtained by saponifying polyvinyl acetate. As PVA, so-called partially saponified PVA in which several tens of acetic acid groups remain, or completely PVA in which only a few % of acetic acid groups remain can be used. PVA between the two can also be used.

[0076] The metal alkoxide used in the coating agent is a compound represented by the general formula M(OR)n (M: Si, Al metal, R: alkyl such as CH3, C2H5). Specifically, tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum Al[OCH(CH3)2]3, etc. can be exemplified. As the silane coupling agent, compounds having an epoxy group such as 3-glycidyloxypropyltrimethoxysilane, compounds having an amino group such as 3-aminopropyltrimethoxysilane, compounds having a mercapto group such as 3-mercaptopropyltrimethoxysilane, compounds having an isocyanate group such as 3-isocyanatepropyltriethoxysilane, and tris-(3-trimethoxysilylpropyl)isocyanurate can be exemplified.

[0077] Polycarboxylic acid polymers are polymers having two or more carboxyl groups in the molecule. Examples of polycarboxylic acid polymers include: (co)polymers of ethylenically unsaturated carboxylic acids; copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers; and acidic polysaccharides having carboxyl groups in molecules such as alginic acid, carboxymethyl cellulose, and pectin. Examples of ethylenically unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of ethylenically unsaturated monomers copolymerizable with ethylenically unsaturated carboxylic acids include: saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconic acid esters, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.

[0078] From the viewpoint of gas barrier properties, it is preferred to include a polymer containing a constituent unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid and crotonic acid among the above-mentioned components, and it is particularly preferred to include a polymer containing a constituent unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid and itaconic acid. In the above-mentioned polymer, the proportion of the constituent unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid and itaconic acid is preferably 80 mol% or more, more preferably 90 mol% or more (wherein the total of all constituent units constituting the polymer is set to 100 mol%). The polymer may be a homopolymer or a copolymer. In the case where the polymer is a copolymer containing other constituent units other than the above-mentioned constituent units, as other constituent units, for example, constituent units derived from ethylenically unsaturated monomers copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid, etc. can be listed.

[0079] The number average molecular weight of the polycarboxylic acid polymer is preferably in the range of 2,000 to 10,000,000, more preferably 5,000 to 1,000,000. When the number average molecular weight is less than 2,000, the water resistance of the gas barrier film is insufficient, the gas barrier property or transparency may be deteriorated by water, or whitening may occur, depending on the application. On the other hand, when the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent becomes high, which may impair the coating property. In the present embodiment, the number average molecular weight is a polystyrene-converted number average molecular weight obtained by gel permeation chromatography (GPC).

[0080] Various additives can be added to the coating agent with polycarboxylic acid polymer as the main component. Crosslinking agent, curing agent, leveling agent, defoaming agent, anti-blocking agent, antistatic agent, dispersant, surfactant, softener, stabilizer, film-forming agent, and thickening agent can be added within the range that does not damage the barrier performance.

[0081] The solvent used in the coating agent with the polycarboxylic acid polymer as the main component is preferably an aqueous medium. As the aqueous medium, water, a water-soluble or hydrophilic organic solvent, or a mixture thereof can be listed. The aqueous medium is usually water, or contains water as the main component. The water content in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more. As the water-soluble or hydrophilic organic solvent, for example, alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; cellosolves; carbitols; and nitriles such as acetonitrile can be listed.

[0082] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of a polycarboxylic acid, and zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, and calcium carbonate, etc. can be listed. These can be used alone or in combination. From the perspective of the oxygen barrier properties of the oxygen barrier coating, zinc oxide particles among the above are preferred. Zinc oxide is an inorganic material with ultraviolet absorption ability. The average particle size of zinc oxide particles is not particularly limited. From the perspective of gas barrier properties, transparency, and coating adaptability, the average particle size is preferably less than 5 μm, more preferably less than 1 μm, and particularly preferably less than 0.1 μm.

[0083] In the case of applying a coating agent with a polyvalent metal compound as the main component and drying it to form a film, as required, in the range of not damaging the effect of the present embodiment, in addition to zinc oxide particles, various additives can also be contained in the coating agent. It is possible to contain a resin that is soluble in or dispersible in the solvent used by the coating agent, a dispersant that is soluble in or dispersible in the solvent, a surfactant, a softener, a stabilizer, a film former, and a tackifier as the additive. Among the above, it is preferred to contain a resin that is soluble in or dispersible in the solvent used by the coating agent. Thus, the coating and film-forming properties of the coating agent are improved. As such a resin, for example, alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluororesins, epoxy resins, and isocyanate resins can be cited. In addition, it is preferred to contain a dispersant that is soluble in or dispersible in the solvent used by the coating agent. Thus, the dispersibility of the polyvalent metal compound is improved. As the dispersant, an anionic surfactant or a nonionic surfactant can be used. Examples of the surfactant include (poly)carboxylates, alkyl sulfate ester salts, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, alkyl phosphates, aromatic phosphates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, alkyl allyl sulfate ester salts, polyoxyethylene alkyl phosphates, sorbitan alkyl esters, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyethylene glycol fatty acid esters, polyoxyethylene sorbitan alkyl esters, polyoxyethylene alkyl allyl ethers, polyoxyethylene derivatives, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene fatty acid esters, and polyoxyethylene alkylamines. These surfactants may be used alone or in combination of two or more. When the coating agent containing a polyvalent metal compound as a main component contains an additive, the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) is preferably in the range of 30:70 to 99:1, more preferably in the range of 50:50 to 98:2.

[0084] As the solvent used in the coating agent with the polyvalent metal compound as the main component, for example, water, methanol, ethanol, isopropanol, n-propanol, n-butanol, n-pentanol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate can be listed. In addition, these solvents can be used alone or in combination of two or more. Among these, from the viewpoint of coating properties, methanol, ethanol, isopropanol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. In addition, from the viewpoint of manufacturability, methanol, ethanol, isopropanol, and water are preferred.

[0085] In the case of forming a film of a polyvalent metal compound after applying a coating agent with a polycarboxylic acid polymer as the main component and drying it to form a film, the polycarboxylic acid polymer can also be preliminarily neutralized with a basic compound to form a part of the carboxyl group. By preliminarily neutralizing a part of the carboxyl group possessed by the polycarboxylic acid polymer, the water resistance and heat resistance of the film composed of the polycarboxylic acid polymer can be further improved. As the basic compound, it is preferred to select at least one basic compound from the group consisting of the above-mentioned polyvalent metal compound, a monovalent metal compound and ammonia. As the monovalent metal compound, for example, sodium hydroxide and potassium hydroxide can be cited.

[0086] When a coating agent mixed with a polycarboxylic acid polymer and a polyvalent metal compound is applied and dried to form a coating film, the coating agent is prepared by mixing a polycarboxylic acid polymer, a polyvalent metal compound, and water or an alcohol as a solvent, and a resin or a dispersant that can be dissolved or dispersed in the solvent, and an additive as required. By applying such a coating agent by a known coating method and drying it, the coating layer 30 can also be formed.

[0087] As the coating method of the coating layer 30, a common coating method can be used. For example, known methods such as dipping, roller coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spraying, gravure offset printing, and organic vapor deposition can be used. Regarding the drying method, one or more combinations of heat application methods such as hot air drying, hot roller drying, high frequency irradiation, infrared irradiation, UV irradiation, and electron beam irradiation can be used. In addition, a transfer method such as adhesive transfer, thermal transfer, and UV transfer can also be used to transfer the film obtained by pre-coating on other resin substrates by the above-mentioned formation method to the gas barrier layer 20.

[0088] The thickness of the coating layer 30 varies depending on the composition of the coating agent used and the coating conditions, and is not particularly limited. However, when the coating layer 30 has a film thickness of less than 0.01 μm after drying, a uniform coating may not be formed, and sufficient gas barrier properties may not be obtained. When the film thickness exceeds 50 μm after drying, cracks are likely to occur in the coating layer 30. Therefore, the appropriate thickness of the coating layer 30 is, for example, in the range of 0.01 to 50 μm, and the optimal thickness of the coating layer 30 is, for example, in the range of 0.1 to 10 μm.

[0089] The gas barrier film 1 having the above-mentioned structure can be widely used to constitute a part of various laminates having barrier properties (hereinafter sometimes collectively referred to as "barrier laminates"). In this case, various layers are provided on the second surface 10b of the substrate layer 10 and the gas barrier layer 20 on the opposite side or on the coating layer 30.

[0090] Therefore, in order to improve the quality of the barrier laminate produced using the gas barrier film 1 , good adhesion with the layer provided on the second surface 10 b is required.

[0091] The inventors conducted various studies to improve the adhesion with the layer provided on the second surface 10b. As a result, it was found that by setting the polar component value of the surface free energy of the second surface to 0.1 mJ / m 2 As described above, it is possible to achieve good adhesion with the layer provided thereon.

[0092] Surface free energy is the energy from the intermolecular forces on the surface. Surface tension is considered to be tension acting on a unit length, while surface free energy is considered to be energy (work) acting on a unit area, and is used to explain the phenomenon that wetting relationships cannot be expressed by the magnitude of surface tension alone. Surface free energy can be calculated based on the contact angle measured with the surface of the object to be measured using multiple (for example, 2 or 3) liquids whose values ​​of the components (polar components, dispersive components) that constitute the surface free energy are known.

[0093] When the gas barrier film 1 is wound into a roll or stored in a plurality of sheets stacked together, sometimes a blocking phenomenon occurs in which adjacent gas barrier films in the thickness direction stick to each other and become difficult to peel off. When blocking occurs, the operation of pulling out the gas barrier film 1 from the roll becomes complicated, and thus the manufacturing efficiency of the barrier laminate using the gas barrier film 1 is reduced.

[0094] The inventors found that by making the polar component value of the surface free energy of the second surface less than 1.3 mJ / m 2 , can reduce the occurrence of adhesion.

[0095] The polar component value of the surface free energy of the second surface 10b can be adjusted by subjecting the second surface 10b to corona treatment, plasma treatment, ozone treatment, or flame treatment, or by forming a coating containing a thermoplastic resin, a thermosetting resin, or an ultraviolet curing resin on the second surface 10b.

[0096] Among the above methods, plasma treatment is particularly preferred from the viewpoint of easy adjustment of the polar component value of the surface free energy. Argon or oxygen can be used for the plasma treatment.

[0097] In the gas barrier film 1 involved in this embodiment, as long as the polar component value of the surface free energy of the second surface 10b satisfies the specified conditions, there is no particular limitation on the material of the second surface. Therefore, if the main component of the base layer 10 is polyethylene or polypropylene, the second surface 10b may also be composed of a layer containing neither polyethylene nor polypropylene.

[0098] The gas barrier film 1 of the present embodiment having the above-mentioned structure exhibits high gas barrier properties. In addition, since polyethylene or polypropylene is used as the main component in the base layer 10, it is also easy to make the ratio of polyethylene or polypropylene in the gas barrier film 1 to be 90% by mass or more. That is, the gas barrier film 1 can easily become a single material with high recyclability, and environmental response can be easily performed.

[0099] Hereinafter, a configuration example of a barrier laminate using the gas barrier film 1 will be described.

[0100] Figure 2 The barrier laminate 101 shown has a configuration in which a heat seal layer 40 capable of thermal fusion bonding is provided on the second surface 10 b of the gas barrier film 1 .

[0101] When two or one folded barrier laminate 101 are heat-sealed at the peripheral portions while the heat seal layers 40 are facing each other, a packaging material such as a bag composed of the barrier laminate 101 can be formed, and a package body in which the contained contents are sealed can be formed.

[0102] As the material of the heat seal layer 40, polypropylene or polyethylene can be used, and it can be a single layer or multiple layers. By making the main component of the heat seal layer 40 the same as that of the substrate layer 10, the barrier laminate 101 can be made of a single material. In this case, the same film as that of the substrate layer 10 can also be used as the heat seal layer 40.

[0103] The polarity (the degree of +- polarization in the molecule) of polyolefin resin components such as polypropylene and polyethylene is extremely small. Therefore, a heat seal layer mainly composed of polypropylene or polyethylene is difficult to bond to the substrate layer 10 by extrusion lamination or dry lamination.

[0104] However, in the gas barrier film 1, since the polar component of the surface free energy of the second surface 10b is 0.1 mJ / m 2 In particular, in dry lamination, the polar component of the surface free energy of the second surface 10b is 0.1 mJ / m 2 As described above, the adhesive uniformly wets and spreads, and an interaction occurs between the molecules constituting the second surface 10b and the adhesive molecules. Thus, the resin film as a heat seal layer is bonded with a high adhesion of more than 1N / 15mm, for example, as measured by a peel strength according to JIS K 6854-2 (180° peeling) or JIS K 6854-3 (T-peeling).

[0105] In addition, the inventors have found that in the gas barrier film 1 having the heat seal layer 40 involved in the present embodiment, by making the peel strength between the substrate layer 10 and the heat seal layer 40 2.0N / 15mm or more in the 180° peel test according to JIS K 6854-2, the adhesion of the second surface 10b of the substrate layer 10 is good, and the occurrence of chain break in the peel test can be suppressed.

[0106] The thickness of the heat seal layer 40 is determined according to the purpose, and can be set to about 15 to 200 μm, for example. The heat seal layer 40 can be bonded to the gas barrier film 1 by dry lamination using an adhesive, or can be provided by extrusion lamination using a fluid resin that becomes a heat seal layer.

[0107] Figure 3 The barrier laminate 102 shown has a structure in which a surface layer 60 is further bonded to the gas barrier layer 20 of the barrier laminate 101 via an adhesive layer 50. The main component of the surface layer 60 may be the same as that of the substrate layer 10. The bonding method of the surface layer 60 may be the same as the bonding method of the above-mentioned heat seal layer 40. It should be noted that at least one of the heat seal layer 40 and the surface layer 60 may be bonded to the gas barrier film 1 via an adhesive.

[0108] The surface layer 60 has a printed layer 61 on one surface, and is bonded so that the printed layer 61 faces the gas barrier layer 20. The printed layer 61 may be provided on the surface of the surface layer 60 opposite to the surface facing the gas barrier layer 20.

[0109] In the case of forming a packaging material using the barrier laminate 101, the gas barrier layer 20 constitutes the outer surface of the packaging material, but in the packaging material formed using the barrier laminate 102, the surface layer 60 constitutes the outer surface of the packaging material. Therefore, by appropriately setting the material of the surface layer 60, various characteristics such as the appearance and scratch resistance of the packaging material can be made into desired contents suitable for the purpose, etc. In addition, the desired appearance and display can be easily given by the printed layer 61. In addition, by bonding the printed layer 61 to the gas barrier layer 20 in a state where it is opposite, the user of the packaging material does not touch the printed layer 61, and the deterioration of the printed layer with the use of the packaging material can be suppressed.

[0110] The configuration of the barrier laminate using the gas barrier film 1 is not limited to the above example. For example, the configuration of the surface layer 60 and the heat seal layer 40 may be reversed; when the barrier laminate is provided with more layers, the heat seal layer 40 may be provided on both sides of the gas barrier film 1. In addition, the coating layer 30 may be provided between the gas barrier layer 20 and the surface layer 60.

[0111] In the gas barrier film of this embodiment, a primer layer (not shown) may be provided between the first surface 10a and the gas barrier layer 20. The primer layer can improve the adhesion between the substrate layer 10 and the gas barrier layer 20, prevent the gas barrier layer 20 from peeling (delamination); or protect the first surface 10a from mechanical damage such as scratches and abrasions during the transportation process before the gas barrier layer is formed. The material of the primer layer is not particularly limited, and examples thereof include thermosetting resins, thermoplastic resins, ultraviolet curable resins, and electron beam curable resins.

[0112] Examples of thermosetting resins for forming the primer layer include thermosetting urethane resins composed of acrylic polyols and isocyanate prepolymers, phenolic resins, urea melamine resins, epoxy resins, unsaturated polyester resins, and silicone resins. Among them, the primer layer formed of a composite of an acrylic polyol containing an OH group and an isocyanate compound having at least two NCO groups in the molecule can significantly improve the adhesion between the substrate layer 10 and the gas barrier layer 20.

[0113] Acrylic polyol is a compound having an OH group at the terminal and side chain among polymer compounds obtained by polymerizing (meth)acrylic acid derivative monomers or polymer compounds obtained by copolymerizing (meth)acrylic acid derivative monomers with other monomers, and reacts with the NCO group of the isocyanate compound. (Meth)acrylic acid derivative monomers have an OH group at the terminal and side chain. Examples of (meth)acrylic acid derivative monomers include hydroxyethyl (meth)acrylate and hydroxybutyl (meth)acrylate.

[0114] The above-mentioned "other monomers" can be copolymerized with (meth)acrylic acid derivative monomers having OH groups at the end and side chains. Examples of "other monomers" include: (meth)acrylic acid derivative monomers having alkyl groups at the side chains, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and tert-butyl (meth)acrylate; (meth)acrylic acid derivative monomers having COOH groups at the side chains, such as (meth)acrylic acid; (meth)acrylic acid derivative monomers having aromatic rings or cyclic structures at the side chains, such as benzyl (meth)acrylate and cyclohexyl (meth)acrylate. In addition to (meth)acrylic acid derivative monomers, styrene monomers, cyclohexylmaleimide monomers, phenylmaleimide monomers, etc. can also be considered. "Other monomers" themselves can have OH groups at the end and side chains.

[0115] The acrylic polyol is particularly preferably a polymer compound obtained by polymerizing a (meth)acrylic acid derivative monomer having a COOH group in a side chain such as (meth)acrylic acid. When forming the primer layer, a composite of an acrylic polyol obtained by polymerizing a monomer having a COOH group and an isocyanate compound can be used to obtain a gas barrier film having higher water vapor barrier properties.

[0116] There is no particular limitation on the acrylic polyol containing OH groups that can be used for the primer layer, but the OH group value is preferably 50 mgKOH / g or more and 250 mgKOH / g or less. Here, the OH group value (mgKOH / g) is an indicator of the amount of OH groups in the acrylic polyol, and represents the number of mg of potassium hydroxide required to acetylate the OH groups in 1 g of the acrylic polyol. In addition, there is no particular limitation on the weight average molecular weight of the acrylic polyol, but specifically, it is preferably 3000 or more and 200000 or less. It is particularly preferably 5000 or more and 100000 or less. In addition, it is more preferably 5000 or more and 40000 or less.

[0117] Isocyanate compounds are compounds having two or more NCO groups in their molecules. Examples of monomeric isocyanates include aromatic isocyanates such as toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), xylene diisocyanate (XDI), and tetramethylxylene diisocyanate (TMXDI); aliphatic isocyanates such as hexamethylene diisocyanate (HDI), methylcyclohexane diisocyanate (H6XDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (H12MDI). In addition, polymers or derivatives of these monomeric isocyanates may also be used. For example, there are trimerized urate types, addition types obtained by reaction with 1,1,1-trimethylolpropane, and biuret types obtained by reaction with biuret.

[0118] The isocyanate compound may be arbitrarily selected from the above-mentioned isocyanate compounds or polymers and derivatives thereof, and may be used alone or in combination of two or more.

[0119] As an example of a primer layer, a solution consisting of a complex of the above-mentioned acrylic polyol and the above-mentioned isocyanate compound and a solvent is applied on the first surface 10a of the substrate layer 10, and the solution is reacted and cured. The equivalent ratio (NCO / OH) of the NCO group of the isocyanate compound to the OH group of the acrylic polyol is preferably 0.3 or more and 2.5 or less. The solvent used here can be any solvent that can dissolve the above-mentioned acrylic polyol and the isocyanate compound. As examples of solvents, methyl acetate, ethyl acetate, butyl acetate, cyclohexanone, acetone, methyl ethyl ketone, dioxolane, tetrahydrofuran, etc. can be listed. It should be noted that, in fact, these solvents can be used in combination of one or more.

[0120] As the thermoplastic resin forming the primer layer, for example, it can be appropriately selected from the following: polyols having two or more OH groups, such as acrylic polyols, polyester polyols, polycarbonate polyols, polyether polyols, polycaprolactone polyols, epoxy polyols; polyethylene resins such as polyvinyl acetate or polyvinyl chloride; polyvinylidene chloride resins; polystyrene resins; polyethylene resins; polypropylene resins; polyurethane resins, etc. In addition, they can be mixed in any ratio. The OH group value of the polyol is not particularly limited, but is preferably 10 mgKOH / g or more and 250 mgKOH / g or less.

[0121] As the ultraviolet curable resin or electron beam curable resin forming the primer layer, as an organic polymer resin, there is no particular limitation, and it is preferred to include at least a resin having an OH group value in the range of 10 to 100 mgKOH / g. In addition, as an organic polymer resin, there is no particular limitation, and it is preferred to include at least a resin having an acid value in the range of 10 to 100 mgKOH / g. Here, the acid value (mgKOH / g) represents the number of mg of potassium hydroxide required to neutralize free fatty acids, resin acids, etc. contained in 1 g of the sample. In addition, as an organic polymer resin, it is preferred to include at least a thermoplastic resin. When the OH group value or the acid value is less than 10 mgKOH / g, the chemical bonding force between the functional group and the surface of the gas barrier layer 20 becomes weak, and the adhesion to the gas barrier layer 20 tends to become low. When the OH group value or the acid value exceeds 100 mgKOH / g, the precipitate containing the OH group produced by the decomposition of the primer layer in durability tests such as moisture and heat resistance tests tends to hinder the adhesion between the primer layer and the gas barrier layer 20.

[0122] As monomers of ultraviolet curable resin or electron beam curable resin that can be used to form the primer layer, for example, monofunctional monomers such as ethyl (meth) acrylate, ethylhexyl (meth) acrylate, styrene, methyl styrene, and N-vinyl pyrrolidone can be used; and polyfunctional monomers such as trimethylolpropane (meth) acrylate, hexanediol (meth) acrylate, tripropylene glycol di(meth) acrylate, diethylene glycol (meth) acrylate, pentaerythritol tri(meth) acrylate, dipentaerythritol hexa(meth) acrylate, 1,6-hexanediol di(meth) acrylate, and neopentyl glycol (meth) acrylate, etc. As oligomers that can be used for the ultraviolet curable resin or electron beam curable resin, there are urethane acrylate, epoxy acrylate, and polyester acrylate, etc.

[0123] When two or more selected from thermosetting resins, thermoplastic resins, ultraviolet curable resins, and electron beam curable resins are used in combination as the organic polymer resin forming the primer layer, the blending ratio is not particularly limited.

[0124] In addition to the organic polymer resin, the primer layer may further include additives as required. Examples of additives include antioxidants, weathering agents, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet light absorbers, plasticizers, antistatic agents, colorants, fillers, surfactants, and silane coupling agents.

[0125] The thickness of the primer layer is preferably 0.05 μm to 7.0 μm. It is particularly preferably 0.05 μm to 0.3 μm. When it is thinner than 0.05 μm, the adhesion between the first surface 10a of the substrate layer 10 and the gas barrier layer 20 becomes insufficient. When it is thicker than 7.0 μm, the influence of internal stress becomes greater, the gas barrier layer 20 cannot be properly laminated, the barrier property becomes insufficient, and the transparency and coating accuracy also become insufficient.

[0126] As the formation method of the primer layer, a common coating method can be used. For example, known methods such as dipping, roller coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spraying, gravure offset printing, and organic vapor deposition can be used. About the drying method, one or more combinations of hot air drying, hot roller drying, high frequency irradiation, infrared irradiation, UV irradiation, and electron beam irradiation can be used. In addition, it can also be such a method: using transfer methods such as adhesive transfer, thermal transfer, and UV transfer, the film obtained by pre-coating on other resin substrates using the above-mentioned formation method is transferred to the first face 10a.

[0127] <Second Embodiment>

[0128] Next, a second embodiment of the present invention will be described. The basic configuration is the same as that of the first embodiment. Therefore, the same configuration is denoted by the same reference numerals and the description thereof is omitted, and only the differences will be described.

[0129] In order to accurately evaluate the adhesiveness of the produced barrier laminate, it is important that chain scission does not occur in a peel test in accordance with JIS K6854-2 or JIS K6854-3.

[0130] The inventors have further studied the constitution that can reduce the occurrence of chain scission between the substrate layer 10 and the bonded layer in the barrier laminate produced using the gas barrier film 1. As a result, it was found that the occurrence of chain scission can be appropriately reduced by constituting the second surface 10b of the substrate layer 10 with a copolymer. Although the mechanism is not completely clear, it is presumed that by constituting the layer with a copolymer, the flexibility of the layer is improved, which helps to prevent fine cracks that cause chain scission from occurring during peeling.

[0131] The copolymer constituting the second surface 10b of the substrate layer 10 may be the copolymer described as the material of the substrate layer 10 in the first embodiment. When the substrate layer 10 is multilayered, the substrate layer 10 may include a layer mainly composed of polypropylene or polyethylene and a layer composed of the copolymer constituting the second surface 10b.

[0132] It should be noted that there is no particular limitation on the type and amount of monomers constituting the copolymer. Therefore, the copolymer may be composed of three or more monomers, and may not contain monomers contained in the bonding layer such as ethylene or propylene.

[0133] Based on the above findings obtained through research, in the gas barrier film according to the present embodiment, the second surface 10b of the substrate layer 10 is formed of a copolymer and the polar component value of the surface free energy of the second surface is set to 0.1 mJ / m 2 As described above, it was successfully achieved to achieve both high adhesion during the preparation of the barrier laminate and suppression of chain scission during the peel test.

[0134] In addition, the inventors have found that in the gas barrier film 1 having the heat seal layer 40 involved in the present embodiment, the peel strength between the substrate layer 10 and the heat seal layer 40 is 1.0 N / 15 mm or more and 7.0 N / 15 mm or less in the 180° peeling according to JIS K 6854-2, and 1.0 N / 15 mm or more and 4.0 mm / 15 mm or less in the T-shaped peeling according to JIS K6854-3, thereby, the adhesion of the second surface 10b of the substrate layer 10 is good, and the occurrence of chain break in the peeling test can be suppressed. When at least one of the peel strengths under the two measurement conditions is less than this range, the adhesion of the second surface 10b of the substrate layer 10 sometimes does not reach the desired strength. In addition, when at least one of the peel strengths under the two measurement conditions is outside this range, there is a portion where the adhesion of the two layers is too weak or too strong, and chain break is easily caused due to the deviation of the adhesion of the bonding surface of the two layers.

[0135] The gas barrier film of the present embodiment will be further described using examples and comparative examples. The technical scope of the present invention is not limited only to the specific contents of the examples and comparative examples.

[0136] (Example 1)

[0137] As the base material layer 10, a three-layer polypropylene film (total thickness 20 μm) having an EVOH layer (thickness 1 μm) on the first side, a copolymer layer (thickness 1 μm) of polypropylene and polyethylene on the second side, and a polypropylene homopolymer layer (thickness 18 μm) in the middle between the first side and the second side was used. The main component of the base material layer is polypropylene.

[0138] SiO was sublimated in a vacuum device, and a gas barrier layer 20 (30 nm in thickness) made of silicon oxide (SiOx) was formed on the EVOH layer by electron beam evaporation.

[0139] Furthermore, the vacuum state was maintained at 67W·sec / m 2 The second surface of the base layer 10 is plasma treated with Ar gas at a plasma treatment intensity of .

[0140] It should be noted that the plasma treatment intensity is calculated by the following formula.

[0141] Plasma treatment intensity = power density [W / m 2 ]×Processing time [sec]

[0142] Power density [W / m 2 ]=input power [W] / cathode area [m 2 ]

[0143] ·Processing time [sec] = electrode MD width [m] / processing speed [m / sec]

[0144] Based on the contact angle values ​​of water and diiodomethane measured using a goniometer (DMs-401 manufactured by Kyowa Interface Science Co., Ltd.), the polar component value of the surface free energy of the second side after the completion of the gas barrier film is calculated. For the contact angle, the amount of each liquid was set to 2.5 μl, and the liquid was measured 1 second after the liquid was applied. The surface free energy (= polar component value + dispersed component value) and the values ​​of its various components were calculated using the commonly used Owens-Wendt-Rabel-Kaelble (WORK, Kaelble-Uy) method. The polar component value of the surface free energy of the second side after plasma treatment is 0.1 mJ / m 2 .

[0145] Next, a coating agent prepared by mixing the following liquid A and liquid B at a mass ratio of 6:4 was applied on the gas barrier layer 20 by gravure coating and dried to form a covering layer 30 having a thickness of 0.4 μm.

[0146] Liquid A: Add 89.6 g of hydrochloric acid (0.1 N) to 10.4 g of tetraethoxysilane and stir for 30 minutes to hydrolyze the mixture to obtain a hydrolyzed solution with a solid content of 3 wt% (converted to SiO2).

[0147] Solution B: 3 wt % water / isopropyl alcohol solution of polyvinyl alcohol (water:isopropyl alcohol weight ratio 90:10) The gas barrier film according to Example 1 was produced as described above.

[0148] (Example 2)

[0149] In addition to setting the plasma treatment intensity to 100 W·sec / m2 Except for this point, a gas barrier film according to Example 2 was produced in the same manner as in Example 1. The polar component value of the surface free energy of the second surface was 0.2 mJ / m 2 .

[0150] (Example 3)

[0151] In addition to setting the plasma treatment intensity to 300 W·sec / m 2 Except for this point, a gas barrier film according to Example 3 was produced in the same manner as in Example 1. The polar component value of the surface free energy of the second surface was 0.4 mJ / m 2 .

[0152] (Example 4)

[0153] In addition to setting the plasma treatment intensity to 500 W·sec / m 2 Except for this point, a gas barrier film according to Example 4 was produced in the same manner as in Example 1. The polar component value of the surface free energy of the second surface was 1.0 mJ / m 2 .

[0154] (Example 5)

[0155] The plasma treatment intensity was set to 100 W·sec / m 2 The gas barrier film of Example 5 was prepared in the same manner as in Example 1 except that the plasma treatment was performed using O2 gas. The polar component value of the surface free energy of the second surface was 1.3 mJ / m 2 .

[0156] (Example 6)

[0157] In addition to setting the plasma treatment intensity to 300 W·sec / m 2 Except for this point, a gas barrier film according to Example 6 was produced in the same procedure as in Example 5. The polar component value of the surface free energy of the second surface was 1.6 mJ / m 2 .

[0158] (Example 7)

[0159] As the substrate layer 10, a two-layer polypropylene film (total thickness 20 μm) was used: a terpolymer (copolymer) layer (thickness 1 μm) composed of polypropylene, polyethylene and 1-butene was provided on the first side, and a homopolymer layer (thickness 19 μm) of polypropylene was provided on the layer below the first side including the second side. The gas barrier film according to Example 7 was prepared in the same manner as in Example 1. The polar component value of the surface free energy of the second side was 0.1 mJ / m 2 .

[0160] (Example 8)

[0161] In addition to setting the plasma treatment intensity to 100 W·sec / m 2 Except for this point, a gas barrier film according to Example 8 was produced in the same procedure as in Example 7. The polar component value of the surface free energy of the second surface was 0.2 mJ / m 2 .

[0162] (Example 9)

[0163] In addition to setting the plasma treatment intensity to 300 W·sec / m 2 Except for this point, a gas barrier film according to Example 9 was produced in the same procedure as in Example 7. The polar component value of the surface free energy of the second surface was 0.8 mJ / m 2 .

[0164] (Example 10)

[0165] In addition to setting the plasma treatment intensity to 500 W·sec / m 2 Except for this point, a gas barrier film according to Example 10 was produced in the same procedure as in Example 7. The polar component value of the surface free energy of the second surface was 1.2 mJ / m 2 .

[0166] (Example 11)

[0167] The plasma treatment intensity was set to 100 W·sec / m 2 The gas barrier film of Example 11 was prepared in the same manner as in Example 7 except that the plasma treatment was performed using O2 gas. The polar component value of the surface free energy of the second surface was 1.9 mJ / m 2 .

[0168] (Example 12)

[0169] In addition to setting the plasma treatment intensity to 300 W·sec / m 2 Except for this point, a gas barrier film according to Example 12 was produced in the same manner as in Example 11. The polar component value of the surface free energy of the second surface was 3.0 mJ / m 2 .

[0170] (Comparative Example 1)

[0171] A gas barrier film according to Comparative Example 1 was produced in the same manner as in Example 1 except that the second surface was not subjected to plasma treatment. The polar component value of the surface free energy of the second surface was 0.0 mJ / m 2 .

[0172] (Comparative Example 2)

[0173] A gas barrier film according to Comparative Example 2 was produced in the same manner as in Example 7 except that the second surface was not subjected to plasma treatment. The polar component value of the surface free energy of the second surface was 0.0 mJ / m 2 .

[0174] The gas barrier films according to Examples and Comparative Examples were evaluated as follows.

[0175] (Evaluation of Adhesion of Second Surface)

[0176] The barrier laminates in each example were prepared by attaching a 70 μm thick unstretched polypropylene film (ZK207 manufactured by Toray) to the second surface of the gas barrier film in each example through dry lamination using a two-component curable polyurethane adhesive to provide a heat seal layer, and by attaching a 20 μm thick stretched polypropylene film (U1 manufactured by Mitsui Chemicals Tohcello Inc.) to the covering layer 30 through dry lamination using a two-component curable polyurethane adhesive to provide a surface layer.

[0177] 180° peeling test pieces were cut out from the barrier laminate of each example according to JIS K 6854-2, and T-peel test pieces were cut out from the barrier laminate of each example according to JIS K 6854-3, and the peel strength between the substrate layer and the heat seal layer was measured using Tensilon Universal Tester RTC-1250 manufactured by Orientec Limited. Both T-peeling and 180° peeling were measured. In both T-peeling and 180° peeling, if the peel strength was 1 N / 15 mm or more, it was considered that the second surface had sufficient adhesion.

[0178] (Adhesion Evaluation)

[0179] Two square samples with a side length of 70 mm were cut out from the gas barrier film of each example and overlapped. A pressure of 200 kg was applied to the overlapped samples using a CO-201 permanent strain tester and blocking tester manufactured by TESTER SANGYO CO., LTD., and the overlapped samples were stored at 50° C. for 2 days.

[0180] Then, according to JIS K 6854-2 and JIS K 6854-3, the peel strength of the upper sample and the lower sample was measured using the automatic curve chart of Shimadzu Corporation. That is, in the blocking evaluation, a peel test between the second surface of the substrate layer of the upper sample and the coating layer of the lower sample was performed. Both T-shaped peeling and 180° peeling were measured. When the peel strength was 0.1N / 15mm or more in any one of the measurements, it was defined as blocking.

[0181] The results are shown in Table 1.

[0182] [Table 1]

[0183]

[0184] In all the examples shown in Table 1, the peel strength in the adhesion evaluation of the second surface was 1N / 15mm or more in T-shaped peeling, which confirmed that the heat seal layer provided on the second surface side was sufficiently adhered to the substrate layer. In Examples 1 to 6 in which the second surface was a copolymer layer, the peel strength was 1N / 15mm or more even in 180° peeling.

[0185] In Examples 7 to 12 where the second surface is a homopolymer layer, the average of the minimum and maximum values ​​of the measured values ​​of 180° peeling is taken as the peel strength, which is all above 1N / 15mm, confirming that the substrate layer and the heat seal layer are sufficiently adhered. It should be noted that in Examples 7 to 12, chain breaking was observed during 180° peeling. Chain breaking refers to the phenomenon that the peeling surface cannot be peeled smoothly, and the peeling strength changes intermittently due to alternating and repeated progress and stop of peeling. In Table 1, the peel strength of the sample in which chain breaking was observed during 180° peeling is marked with (*).

[0186] In the 180° peeling in the adhesion evaluation of the second surface, in Examples 1 to 6 satisfying 2.0 N / 15 mm or more, it is found that the adhesion of the second surface 10 b of the base layer 10 is good and the occurrence of chain breakage in the peeling test can be suppressed.

[0187] In addition, the polar component value of the surface free energy on the second surface is less than 1.3 mJ / m 2 In Examples 1 to 4 and Examples 7 to 10, the peel strength in the blocking evaluation was less than 0.1 N / 15 mm in both the T-shape and 180°, and chain scission was sufficiently suppressed.

[0188] On the other hand, in Comparative Examples 1 and 2, although chain scission did not occur, the peel strength value in the adhesion evaluation of the second surface was low, and the adhesion between the base material layer and the heat seal layer was insufficient.

[0189] The present invention is described in more detail below using other embodiments. The technical scope of the present invention is not limited in any way based on the specific contents of these embodiments.

[0190] (Example 2-1)

[0191] As the base material layer 10, a three-layer polypropylene film (total thickness 20 μm) was used: an EVOH layer (thickness 1 μm) was provided on the first side, a copolymer layer (thickness 1 μm) composed of a terpolymer of propylene, ethylene and 1-butene was provided on the second side, and a polypropylene homopolymer layer (thickness 18 μm) was provided in the middle between the first side and the second side. The main component of the base material layer was polypropylene.

[0192] SiO was sublimated in a vacuum device, and a gas barrier layer 20 (30 nm in thickness) made of silicon oxide (SiOx) was formed on the EVOH layer by electron beam evaporation.

[0193] In addition, the vacuum state was maintained and an RIE (Reactive Ion Etching) processing device was used to process the etched particles at 83 W·sec / m 2 The second surface of the base layer 10 is plasma treated with Ar gas at a plasma treatment intensity of .

[0194] It should be noted that the plasma treatment intensity is calculated by the following formula.

[0195] Plasma treatment intensity = power density [W / m 2 ]×Processing time [sec]

[0196] Power density [W / m 2 ]=input power [W] / cathode area [m 2 ]

[0197] ·Processing time [sec] = electrode MD width [m] / processing speed [m / sec]

[0198] Next, a coating agent prepared by mixing the following liquid A and liquid B at a mass ratio of 6:4 was applied on the gas barrier layer 20 by gravure coating and dried to form a covering layer 30 having a thickness of 0.4 μm.

[0199] Liquid A: Add 89.6 g of hydrochloric acid (0.1 N) to 10.4 g of tetraethoxysilane and stir for 30 minutes to hydrolyze the solution to obtain a hydrolyzed solution with a solid content of 3 wt% (converted to SiO2)

[0200] Liquid B: 3 wt% water / isopropanol solution of polyvinyl alcohol (water:isopropanol weight ratio 90:10)

[0201] In the above manner, a gas barrier film according to Example 2-1 was produced.

[0202] Based on the contact angle values ​​of water and diiodomethane measured using a goniometer (DMs-401 manufactured by Kyowa Interface Science Co., Ltd.), the polar component value of the surface free energy of the second side after the completion of the gas barrier film is calculated. For the contact angle, an appropriate amount of each liquid is set to 2.5 μl, and the liquid is measured 1 second after the liquid is applied. The surface free energy (= polar component value + dispersed component value) and the values ​​of its various components are calculated using the commonly used Owens-Wendt-Rabel-Kaelble (WORK, Kaelble-Uy) method. The polar component value of the surface free energy of the second side is 0.1 mJ / m 2 .

[0203] (Example 2-2)

[0204] The copolymer layer on the second surface was formed of a copolymer of propylene and ethylene, and a magnetron sputtering discharge device (MF processing device) using an MF power supply was used at 331 W·sec / m 2 The gas barrier film of Example 2-2 was prepared in the same manner as Example 2-1 except that the treatment intensity was increased and plasma treatment was performed using O2 gas. The polar component value of the surface free energy of the second surface was 0.2 mJ / m 2 .

[0205] (Example 2-3)

[0206] In addition to setting the plasma treatment intensity to 993W·sec / m 2 Except for this point, the gas barrier film according to Example 2-3 was produced in the same procedure as in Example 2-2. The polar component value of the surface free energy of the second surface was 0.3 mJ / m 2 .

[0207] (Example 2-4)

[0208] The copolymer layer on the second surface side was formed of a copolymer of propylene and ethylene, and the plasma treatment intensity was set to 300 W·sec / m 2 , except for this, the gas barrier film according to Example 2-4 was prepared in the same manner as in Example 2-1. The polar component value of the surface free energy of the second surface was 0.4 mJ / m 2 .

[0209] (Example 2-5)

[0210] In addition to setting the plasma treatment intensity to 500 W·sec / m 2 Except for this point, the gas barrier film according to Example 2-5 was produced in the same procedure as Example 2-4. The polar component value of the surface free energy of the second surface was 1.0 mJ / m 2 .

[0211] (Example 2-6)

[0212] The copolymer layer on the second surface side was formed of a copolymer of propylene and ethylene, and O2 gas was used at 100 W·sec / m 2 The gas barrier film of Example 2-6 was prepared in the same manner as in Example 2-1 except that the plasma treatment was performed at a treatment intensity of 1.3 mJ / m 2 .

[0213] (Example 2-7)

[0214] In addition to setting the plasma treatment intensity to 500 W·sec / m 2 Except for this point, the gas barrier film according to Example 2-7 was produced in the same procedure as Example 2-1. The polar component value of the surface free energy of the second surface was 1.5 mJ / m 2 .

[0215] (Comparative Example 2-1)

[0216] A gas barrier film according to Comparative Example 2-1 was produced in the same manner as in Example 2-1 except that the second surface was not subjected to plasma treatment. The polar component value of the surface free energy of the second surface was 0.0 mJ / m 2 .

[0217] (Comparative Example 2-2)

[0218] A gas barrier film according to Comparative Example 2-2 was produced in the same manner as in Example 2-2 except that the second surface was not subjected to plasma treatment. The polar component value of the surface free energy of the second surface was 0.0 mJ / m 2 .

[0219] (Comparative Example 2-3)

[0220] A gas barrier film according to Comparative Example 2-3 was prepared in the same manner as in Example 2-1, except that the thickness of the polypropylene homopolymer layer was set to 19 μm and no copolymer layer was provided on the second surface. The polar component value of the surface free energy of the second surface was 0.0 mJ / m 2 .

[0221] (Comparative Example 2-4)

[0222] A gas barrier film according to Comparative Example 2-4 was prepared in the same manner as in Example 2-3 except that the thickness of the polypropylene homopolymer layer was set to 19 μm and no copolymer layer was provided on the second surface. The polar component value of the surface free energy of the second surface was 0.3 mJ / m 2 .

[0223] (Comparative Example 2-5)

[0224] The thickness of the polypropylene homopolymer layer was set to 19 μm, no copolymer layer was provided on the second surface, and the plasma treatment intensity was set to 1325 W·sec / m 2 , except for this, a gas barrier film according to Comparative Example 2-5 was prepared in the same manner as in Example 2-2. The polar component value of the surface free energy of the second surface was 0.4 mJ / m 2 .

[0225] (Comparative Example 2-6)

[0226] The thickness of the polypropylene homopolymer layer was set to 19 μm, no copolymer layer was provided on the second surface, and O2 gas was used at 83 W·sec / m 2 The gas barrier film of Comparative Example 2-6 was prepared in the same manner as in Example 2-1 except that the plasma treatment was performed at a treatment intensity of 1.2 mJ / m 2 .

[0227] (Comparative Example 2-7)

[0228] In addition to setting the plasma treatment intensity to 300 W·sec / m 2 Except for this point, a gas barrier film according to Comparative Example 2-7 was produced in the same procedure as Comparative Example 2-6. The polar component value of the surface free energy of the second surface was 2.0 mJ / m 2 .

[0229] (Comparative Example 2-8)

[0230] In addition to setting the plasma treatment intensity to 500 W·sec / m 2 Except for this point, the gas barrier film according to Comparative Example 2-8 was produced in the same procedure as Comparative Example 2-7. The polar component value of the surface free energy of the second surface was 3.8 mJ / m 2 .

[0231] The gas barrier films according to Examples and Comparative Examples were evaluated as follows.

[0232] (Evaluation of Adhesion of Second Surface)

[0233] By dry lamination using a two-component curable polyurethane adhesive, a 70 μm thick unstretched polypropylene film (ZK207 manufactured by Toray) was adhered to the second surface of the gas barrier film involved in each example to provide a heat seal layer, and further, by dry lamination using a two-component curable polyurethane adhesive, a 20 μm thick stretched polypropylene film (U1 manufactured by Mitsui Chemicals Tohcello Inc.) was adhered to the covering layer 30 to provide a surface layer, thereby producing the barrier laminate involved in each example.

[0234] 180° peeling test pieces were cut out from the barrier laminate of each example according to JIS K 6854-2, and T-peel test pieces were cut out from the barrier laminate of each example according to JIS K 6854-3, and the peel strength between the substrate layer and the heat seal layer was measured using Tensilon Universal Tester RTC-1250 manufactured by Orientec Limited. Both T-peeling and 180° peeling were measured. In both T-peeling and 180° peeling, if the peel strength was 1 N / 15 mm or more, it was considered that sufficient adhesion was present on the second surface.

[0235] (Adhesion Evaluation)

[0236] Two square samples with a side length of 70 mm were cut out from the gas barrier film of each example and overlapped. A pressure of 200 kg was applied to the overlapped samples using a CO-201 permanent strain tester and blocking tester manufactured by TESTER SANGYO CO., LTD., and the overlapped samples were stored at 50° C. for 2 days.

[0237] Then, according to JIS K 6854-2 and JIS K 6854-3, the peel strength of the upper sample and the lower sample was measured using the automatic curve chart of Shimadzu Corporation. That is, in the blocking evaluation, a peel test was performed between the second surface of the substrate of the upper sample and the coating layer of the lower sample. The two types of T-shaped peeling and 180° peeling were measured. When the peel strength was shown to be 0.1N / 15mm or more in any one of the measurements, it was defined as the occurrence of blocking.

[0238] The results are shown in Table 2.

[0239] [Table 2]

[0240]

[0241] In all the examples shown in Table 2, the peel strength in the adhesion evaluation of the second surface was 1N / 15mm or more in both the T-shape and the 180° shape, and it can be confirmed that the heat seal layer provided on the second surface side is sufficiently adhered to the substrate layer. In addition, the polar component value of the surface free energy on the second surface is less than 1.3mJ / m 2 In Examples 2-1 to 2-5, the peel strength in the blocking evaluation was less than 0.1 N / 15 mm in both the T-shape and the 180° shape, and blocking was sufficiently suppressed.

[0242] On the other hand, in Comparative Examples 2-1 and 2-3, the peel strength value in the adhesion evaluation of the second surface was low, and the adhesion between the base material layer and the heat seal layer was insufficient.

[0243] In Comparative Examples 2-4 to 2-8, where the second surface is a homopolymer layer, chain scission was observed in which low and high values ​​of peel strength were repeated in the 180° peeling in the adhesion evaluation of the second surface. As an example, Figure 4 This is a graph showing the 180° peel measurement chart of Comparative Example 2-5 in which the chain scission phenomenon occurred.

[0244] Here, the chain breaking phenomenon refers to the phenomenon that the peeling surface cannot be peeled off smoothly, and the peeling strength changes intermittently by alternately repeating the progress and stop of peeling. In addition, it is believed that the chain breaking phenomenon is likely to occur in the following cases: within the bonding surface of the two layers, the sealing strength in the peeling progress direction is not constant, and the sealing strength has deviations depending on the location. It is believed that a barrier laminate with a deviation in the sealing strength between the substrate layer and the heat-sealing layer may break from a location with weak sealing strength. Therefore, by confirming the presence or absence of the chain breaking phenomenon, the uniformity of the adhesion of the second surface of the barrier laminate and the uniformity of the broken bag strength can be confirmed.

[0245] It should be noted that in Comparative Examples 2-4 to 2-8 of Table 2, since chain breaking was observed, the minimum and maximum values ​​of the peel strength are shown in the column of the measurement results of 180° peeling for the adhesion evaluation on the second surface. According to the results of Comparative Examples 2-4 to 2-8, when the difference between the maximum and minimum values ​​of the peel strength is 0.3N / 15mm or more, it can be judged that a chain breaking phenomenon has occurred. It should be noted that in Examples 2-1 to 2-7 and Comparative Examples 2-1 to 2-3, the difference between the maximum and minimum values ​​of the peel strength is small, and no chain breaking phenomenon was observed in the test, so Table 2 shows the average value of the measured values ​​as the peel strength. According to the evaluation results shown in Table 2, it can be considered that when the difference between the maximum and minimum values ​​of the peel strength in 180° peeling is less than 0.3N / 15mm, chain breaking is difficult to occur.

[0246] In Comparative Example 2-8, the polar component value of the surface free energy of the second surface was 1.3 mJ / m 2 In addition, adhesion also occurs.

[0247] Although one embodiment and examples of the present invention have been described above, the specific configuration is not limited to the embodiment, and changes and combinations of the configurations are also included within the scope that does not depart from the gist of the present invention.

[0248] Explanation of symbols

[0249] 1 Gas barrier film

[0250] 10. Base material layer

[0251] 10a Side 1

[0252] 10b Side 2

[0253] 20 Gas barrier layer

[0254] 30 Coating layer

[0255] 40 heat seal layer

[0256] 60 Surface

[0257] 61 Printing layer

[0258] 101, 102 Barrier laminate

Claims

1. A gas barrier film comprising: A substrate layer with polypropylene or polyethylene as the main component; A gas barrier layer formed on the first surface side of the base layer; and A heat seal layer mainly composed of polypropylene or polyethylene is formed on the second surface opposite to the first surface. The peel strength between the substrate layer and the heat seal layer 1.0 N / 15 mm or more and 7.0 N / 15 mm or less in 180° peeling according to JIS K 6854-2, In T-peeling according to JIS K 6854-3, it is 1.0 N / 15 mm or more and 4.0 mm / 15 mm or less.

2. The gas barrier film according to claim 1, wherein The polar component value of the surface free energy of the second surface opposite to the first surface is 0.1 mJ / m 2 above.

3. The gas barrier film according to claim 1, wherein The second surface opposite to the first surface is composed of a copolymer, and the polar component value of the surface free energy is 0.1 mJ / m 2 above.

4. The gas barrier film according to any one of claims 1 to 3, wherein The polar component value of the surface free energy of the second surface is less than 1.3 mJ / m 2 .

5. The gas barrier film according to any one of claims 1 to 3, wherein The gas barrier layer contains at least one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metal aluminum, and aluminum oxide.

6. The gas barrier film according to any one of claims 1 to 3, wherein The first surface is made of any one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, a composite of polypropylene, polyethylene and α-olefin, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer.

7. The gas barrier film according to any one of claims 1 to 3, further comprising a coating layer formed on the gas barrier layer. The coating layer contains any one of a metal alkoxide, a hydrolyzate of a metal alkoxide, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, and a polyvalent metal salt of a carboxylic acid which is a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound.

8. The gas barrier film according to any one of claims 1 to 3, further comprising a primer layer provided between the first surface and the gas barrier layer, The primer layer includes at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet curable resin, and an electron beam curable resin.

9. The gas barrier film according to claim 1 or 2, wherein The peel strength between the substrate layer and the heat seal layer is 2.0 N / 15 mm or more and 7.0 N / 15 mm or less in 180° peeling according to JIS K 6854-2.

10. The gas barrier film according to claim 3, wherein The difference between the maximum value and the minimum value of the peel strength in the 180° peeling is less than 0.3 N / 15 mm.

11. A barrier laminate comprising: The gas barrier film according to any one of claims 1 to 3; and The heat seal layer has the same main component as the base material layer and is bonded to the gas barrier film. 12 . The barrier laminate according to claim 11 , further comprising a surface layer having the same main component as that of the base layer and bonded to the gas barrier film.

13. The barrier laminate according to claim 12, wherein At least one of the heat seal layer and the surface layer is bonded to the gas barrier film via an adhesive.

14. The barrier laminate according to claim 12, wherein: The surface layer has a printed layer on at least one side.

Citation Information

Patent Citations

  • Game machine

    JP2022111829A

  • Game machine

    JP2022111830A

  • Laminate film, barrier laminate film, and gas-barrier packaging material and gas-barrier packaged body each using said barrier laminate film

    WO2019087960A1

  • Multilayer body

    CN101511585A

  • Air-blocking and water-blocking laminated film for packaging and application of air-blocking and water-blocking laminated film in food packaging

    CN114479153A